Fractional operators with homogeneous kernels in weighted Herz spaces with variable exponent. Issue 6 (13th April 2022) - Abdalmonem, Afif; Scapellato, Andrea
Abstract : Let Ω ∈ L s ( S n − 1 ), with s ≥ 1, be a homogeneous function of degree zero. In this paper, we establish the boundedness of the homogeneous fractional integral operator on weighted Herz spaces with variable exponent K ˙ p ( ⋅ ) α, q ( w ) .